2006
DOI: 10.1002/cbdv.200690063
|View full text |Cite
|
Sign up to set email alerts
|

Peptaibiomics: Screening for Polypeptide Antibiotics (Peptaibiotics) from Plant-ProtectiveTrichoderma Species

Abstract: were selected because of their antagonistic potential against Eutypa dieback and Esca which are fungal diseases of grapevine trunks. These isolates were screened for the production of a group of polypeptide antibiotics named peptaibiotics, including its subgroups peptaibols and lipopeptaibols. Fully-grown fungal cultures on potato-dextrose agar were extracted with CH 2 Cl 2 /MeOH, and these extracts were subjected to SPE using C 18 cartridges. The methanolic eluates were analyzed by on-line LC/ESI-MS n couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
5

Year Published

2007
2007
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 57 publications
(68 reference statements)
1
60
0
5
Order By: Relevance
“…Compared to the recently described peptaibiomics approach (Degenkolb et al, 2006a;Krause et al, 2006), our approach only partially identifies the peptaibols, but the information can be obtained from extremely small amounts of biomass and much more rapidly. Below, we discuss the consistency of our data with the available structural data and the implications of molecular genetic data for the study of the evolution of these NRPS systems.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared to the recently described peptaibiomics approach (Degenkolb et al, 2006a;Krause et al, 2006), our approach only partially identifies the peptaibols, but the information can be obtained from extremely small amounts of biomass and much more rapidly. Below, we discuss the consistency of our data with the available structural data and the implications of molecular genetic data for the study of the evolution of these NRPS systems.…”
Section: Discussionmentioning
confidence: 99%
“…brevicompactum, the same study describes trichocompactins and trichobrevins in CBS In a recent peptaibiomics study, plant-protective Trichoderma strains of different origins (T. strigosum, T. pubescens and T. stromaticum) were compared (Degenkolb et al, 2006a). The authors concluded from the differences between the strains and similarities between different species that peptaibol sequences are of limited relevance for chemotaxonomy.…”
Section: Peptaibols In Trichodermamentioning
confidence: 99%
See 3 more Smart Citations